2009
DOI: 10.1007/s10551-009-0156-3
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Forces of Socially Responsible Supply Chain Management Orientation

Abstract: supply chain, clothing, sweatshop, social responsibility,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 39 publications
1
126
1
1
Order By: Relevance
“…First, it responds to the call for empirical studies demonstrating how socially responsible procurement practices are adopted (Ashby et al 2012). Quantitative studies of the drivers and outcomes of social responsibility are rare (Ehrgott et al 2011;Park-Poaps and Rees 2010) and this is the first study to use structural equation modeling in order to understand how bases of power impact the adoption of socially responsible procurement practices by first-tier suppliers.…”
Section: Resultsmentioning
confidence: 99%
“…First, it responds to the call for empirical studies demonstrating how socially responsible procurement practices are adopted (Ashby et al 2012). Quantitative studies of the drivers and outcomes of social responsibility are rare (Ehrgott et al 2011;Park-Poaps and Rees 2010) and this is the first study to use structural equation modeling in order to understand how bases of power impact the adoption of socially responsible procurement practices by first-tier suppliers.…”
Section: Resultsmentioning
confidence: 99%
“…This is because, pragmatically, the internal indicators are much more within the scope of control of the reporting respondent. It is also, however, because it is quite reasonable to assume that in many cases, activities conducted within the supply chains are those activities to which the MNCs seek labour cost advantages in choosing not to conduct such activities in-house -with the associated implication that lower cost is linked to a lower commitment to HRM (Hofmann, Busse, Bode, & Henke, 2014;Park-Poaps & Rees, 2010). Hence: Hypothesis 2.…”
Section: Hypothesesmentioning
confidence: 99%
“…Predominantly, papers evaluated industry peers (14) such as non-governmental organizations (NGOs), including multi-stakeholder initiatives (MSI), and activist campaigns (e.g., [65]). To sum up, scholars constantly state that NGOs can act as watchdogs and are targeting the focal companies, which motivates them to implement social risk management practices (17) [66].…”
Section: Driversmentioning
confidence: 99%
“…Also, public or governmental regulations as drivers have found scant attention since 2005. Only five studies have been identified [3,43,65,70,79]. Regarding media pressures, one study discusses predominantly the powerful impact of the media and its threats on companies' public image and financial well-being [65].…”
Section: Driversmentioning
confidence: 99%
See 1 more Smart Citation